Cultural elements in Chinese animation characters: A systematic review of their visual, narrative, and communicative roles - Luo, Yuye; Bakar, Juliana Aida Abu; Yusoff, Mohd Fitri (Edelweiss Applied Science and Technology, 2025)
As an important carrier of cultural communication and artistic expression, animation has gradually formed a unique style and charm in the process of development in China. Cultural elements in Chinese animation character design not only give characters distinct personalities and rich meanings, but also build a bridge of emotional resonance and cultural inheritance between audiences and works. An in-depth study of this topic helps to explore the potential of Chinese animation and improve its influence in the domestic and international cultural markets. This study aims to explore the application of cultural elements in Chinese animation character design, in order to enhance cultural expression and global communication. A systematic literature review (SLR) was conducted to collect and analyze relevant studies from 1945 to 2024. The review summarizes how cultural elements function in visual presentation, narrative structure, and cultural communication. The findings show that cultural elements play a significant role in shaping character identity, strengthening emotional connection, and conveying values. However, existing research still faces problems such as vague classification and a lack of empirical studies. This study deepens the understanding of the role of cultural elements in character design and provides theoretical and practical references for animation creators. It also promotes the global dissemination and recognition of Chinese culture through animation.